Different types of experiences’ influence on younger consumer satisfaction and loyalty in the process of traditional beverage-selling industry’s development ---based on new-style tea industry in China - Yin, Chenjie (2022)
In the experience economy era, experience has become more and more important in people's daily life. With the increase of people's income and the development of productivity, consumers no longer just pay attention to the utility or function of the products, but try to experience fantasies, feelings, and fun generated in the consuming process. Nowadays, not only the pure service-providing company, but also some products-selling enterprises begin to focus on the creating experience for their consumers to enhance their competitiveness in the industry. Traditional product-selling industries are facing the difficulty of attracting young consumers. Although young consumers present high respect and acceptability to the traditional product, the traditional products’ consumption of young generation is still decreasing. Chinese tea industry is a typical traditional beverage-selling industry which has the difficulty, the main consumers who purchase traditional tea products (e.g., bulk tea, packaged tea) are the middle-aged and the elderly, the industry barely have young consumers. However, the rise of the new-style tea industry is an interesting phenomenon, which attracts many young consumers to purchase tea-related drinks and products. this provides an entry point to investigate different types of experience’s influence on younger consumers in the process of traditional beverage-selling industry’s development.